ANALYSIS GENDER LANGUAGE DIFFERENCES FOUNDED IN MARSHANDA AND SIENNA KASYAFANI BY DANIEL MANANTA NETWORK PODCAST - Febriani, Aulia; Dalpah, Dalpah; Sari, Sekar Wulan; Nargis, Nargis (VARIABLE RESEARCH JOURNAL, 2025)
This research analyzes gender-based language differences in Daniel Mananta Network's podcast episode “Blak-Blakan! Ngobrol Bareng Marshanda & Sienna Kasyafani #Part5.” This study aims to identify language features that reflect gender differences, such as politeness, emotional expression, and communication style. Using a descriptive qualitative approach, data was collected through observation and transcription of conversations. The results of the analysis show that women more often use polite language, soft intonation, intensifiers, and emotional expressions, while men are more assertive, direct, and simple. Social factors such as cultural norms and gender roles influence these differences.  This study found that interactions in podcasts reflect social dynamics that demonstrate gender roles in informal communication. This research provides important insights into gender variation in language use in Indonesia, particularly in the context of digital media..